1990
DOI: 10.1021/bi00455a028
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of membrane-reconstituted yeast cytochrome c oxidase

Abstract: The thermal dependence of the structural stability of membrane-reconstituted yeast cytochrome c oxidase has been studied by using different techniques including high-sensitivity differential scanning calorimetry, differential detergent solubility thermal gel analysis, and enzyme activity measurements. For these studies, the enzyme has been reconstituted into dimyristoylphosphatidylcholine (DMPC) and dielaidoylphosphatidylcholine (DEPC) vesicles using detergent dialysis. The phospholipid moiety affects the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 20 publications
6
43
0
Order By: Relevance
“…This experiment rules out the possibility of overlapping independent transitions. Thus, at a scan rate 59.6 K/h, AChE demonstrates a single thermal transition within a narrow temperature range.A similar asymmetry of the DSC peak has been observed for several proteins that undergo irreversible thermal transition, including thermolysin, cytochrome c oxidase, carboxypeptidase B, phosphoglycerate kinase, G-actin, and 8-kDa sea anemone cytotoxin (Sanchez-Ruiz et al, 1988;Morin et al, 1990;Conejero-Lara et al, 1991a, 1991bGalisteo et al, 1991;Le Bihan & Gicquaud, 1993;Zhadan & Shnyrov, 1994). In all these cases, the behavior of the systems was described as a thermal denaturation process under kinetic control.…”
supporting
confidence: 59%
“…This experiment rules out the possibility of overlapping independent transitions. Thus, at a scan rate 59.6 K/h, AChE demonstrates a single thermal transition within a narrow temperature range.A similar asymmetry of the DSC peak has been observed for several proteins that undergo irreversible thermal transition, including thermolysin, cytochrome c oxidase, carboxypeptidase B, phosphoglycerate kinase, G-actin, and 8-kDa sea anemone cytotoxin (Sanchez-Ruiz et al, 1988;Morin et al, 1990;Conejero-Lara et al, 1991a, 1991bGalisteo et al, 1991;Le Bihan & Gicquaud, 1993;Zhadan & Shnyrov, 1994). In all these cases, the behavior of the systems was described as a thermal denaturation process under kinetic control.…”
supporting
confidence: 59%
“…3). As a rescan of the same protein sample displayed no endothermic signal, this thermal denaturation was found to be irreversible, which is consistent with the results obtained from the yeast and Paracoccus denitrificans aa 3 -CcOs (37,38). Because of the irreversible nature of the thermal denaturation process, the calorimetric data cannot be directly analyzed in terms of equilibrium thermodynamics (39).…”
Section: Resultssupporting
confidence: 81%
“…The kinetically controlled character of irreversible protein denaturation had been deduced from calorimetric studies for this and other membrane proteins [4,5,13]; however, the present paper provides direct structural evidence that this is the case (see mainly Fig. 3).…”
Section: Discussionmentioning
confidence: 58%
“…The intramembranous regions of those proteins are believed to be stable mainly because of hydrogen bonds formed within the hydrophobic membrane matrix [1][2][3]. Calorimetric studies of membrane protein stability have shown that, at least in some cases, thermal denaturation is a kinetically controlled irreversible process, in which the observed transition temperature is a function of the experimental heating rate [4,5]. Recent data on the thermal denaturation of bovine and Paracoccus cytocrome c oxidases [2,3] suggest that most of the intramembranous secondary structure is maintained even above denaturation temperatures.…”
Section: Introductionmentioning
confidence: 99%